The use of behavior contracting as classroom management approach for socially-alienated children - Maranan, Estelita Mariano 1943- (College of Education, University of the Philippines Diliman, 1977)
This study attempted to focus attention on the use of behavior contracts to be able to determine what behavior contracting is, how it can be used as a classroom management approach, what behavior problems of children it can address, and what therapeutic values can be derived from behavior contracting. Some basic behavior modification principles and procedures were adopted and discussed. These were the identification of the observable behavior to be monitored, establishment of a strategy for recording the observed behavior, establishment of a criterion against which to compare observations, identification of the consequences of or reinforcements for change, and identification of a time span within which change can reasonably be expected to occur. Because of the orderly and structured response, this approach can be effectively used as a therapeutic measure for socially-alienated children once properly conceived, administered, and implemented.